PENGEMBANGAN MEDIA PEMBELAJARAN CERNAKU BERBANTUAN GENIALLY DENGAN MODEL PROJECT BASED LEARNING MATA PELAJARAN IPAS MATERI ORGAN PENCERNAAN MANUSIA KELAS V SDN 3 CAMPURDARAT KABUPATEN TULUNGAGUNG - Dellia Oktiva Maharani; Ammy Aulia Renata Anny (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The limited use of interactive digital media and the predominant reliance on textbooks in Natural and Social Sciences (IPAS) learning make abstract topics, such as the human digestive system, difficult for elementary school students to visualize and understand. This study aimed to develop and determine the validity and practicality of CERNAKU (My Digestive Story), a Genially-assisted learning medium integrated with the Project-Based Learning (PjBL) model for teaching the human digestive system. This study employed the Research and Development (R&D) method using the ADDIE model. The participants were 22 fifth-grade students at SD Negeri 3 Campurdarat, consisting of 5 students in the small-group trial and 17 students in the large-group trial. Data were collected through observation, expert validation, questionnaires, and documentation and were analyzed using quantitative and qualitative descriptive analyses. The results showed that CERNAKU achieved validity scores of 95% from media experts and 91% from material experts, both of which were categorized as highly valid. The practicality assessment yielded scores of 89% in the small-group trial, 92.3% in the large-group trial, and 94% based on the teacher’s response, all of which were categorized as highly practical. The novelty of CERNAKU lies in its integration of story-based content, Genially-based interactive multimedia, and concrete project activities within a unified IPAS learning experience. These findings indicate that CERNAKU, assisted by Genially and integrated with the PjBL model, is highly valid and practical for teaching the human digestive system to fifth-grade elementary school students.